PENGARUH GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK MUHAMMADIYAH 2 PALERAN - Iwanda Fatma Sari; Sofyan Rofi; Bahar Agus Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Islamic Religious Education (PAI) Teacher's Role on Students' Learning Motivation at SMK Muhammadiyah 2 Paleran. The research employed a quantitative descriptive approach using simple linear regression analysis. The research population consisted of 68 students in grade XI from three vocational programs: Software Engineering, Motorcycle Engineering, and Digital Business. Data were collected through questionnaires using a five-point Likert scale, supplemented by observation and documentation. Instrument validity was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha. Prerequisite tests included the Kolmogorov-Smirnov normality test and the Test of Linearity. The results of data analysis yielded the regression equation Y = 32.596 + 0.549X. The partial t-test obtained a t-count of 8.268 with a significance value of 0.000 < 0.05, indicating that the PAI Teacher's Role variable has a positive and significant effect on Students' Learning Motivation. The coefficient of determination (R Square) of 0.509 reveals that the PAI Teacher's Role accounts for 50.9% of the variance in Students' Learning Motivation, while the remaining 49.1% is influenced by other factors outside this study. Keywords: Teacher's Role PAI, Learning Motivation, Simple Linear Regression This study aims to determine the effect of the Islamic Religious Education (PAI) Teacher's Role on Students' Learning Motivation at SMK Muhammadiyah 2 Paleran. The research employed a quantitative descriptive approach using simple linear regression analysis. The research population consisted of 68 students in grade XI from three vocational programs: Software Engineering, Motorcycle Engineering, and Digital Business. Data were collected through questionnaires using a five-point Likert scale, supplemented by observation and documentation. Instrument validity was tested using Pearson Product Moment correlation and reliability using Cronbach's Alpha. Prerequisite tests included the Kolmogorov-Smirnov normality test and the Test of Linearity. The results of data analysis yielded the regression equation Y = 32.596 + 0.549X. The partial t-test obtained a t-count of 8.268 with a significance value of 0.000 < 0.05, indicating that the PAI Teacher's Role variable has a positive and significant effect on Students' Learning Motivation. The coefficient of determination (R Square) of 0.509 reveals that the PAI Teacher's Role accounts for 50.9% of the variance in Students' Learning Motivation, while the remaining 49.1% is influenced by other factors outside this study. Keywords: Teacher's Role PAI, Learning Motivation, Simple Linear Regression